Method for producing olivine-type lithium phosphate-based positive electrode active material
By using trilithium acid as the core during the synthesis process and performing microwave radiation synthesis within a specific temperature range, the problem of difficult particle size control of the cathode active material in the prior art is solved, and the efficient and stable preparation of olive-type lithium-ferric acid cathode active material is achieved, thereby improving battery performance and manufacturing efficiency.
Patent Information
- Application Number
- JP2021035433
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-05
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2041-03-05
AI Technical Summary
In the prior art, when synthesis is performed using microwave radiation, it is difficult to effectively control the particle size of the positive electrode active material, resulting in poor battery performance.
By using trilithium acid (Li3PO4) as the core, its specific surface area is controlled to be in the range of 10m2/g~200m2/g, and synthesized under microwave radiation from 80°C to 120°C, an olive-type lithium-ferric acid positive electrode active material with excellent battery performance was prepared.
Effective control of the particle size of the positive electrode active material is achieved, the overall performance of the battery is improved, and manufacturing efficiency is improved.
Smart Images

Figure 0007649167000001 
Figure 0007649167000002 
Figure 0007649167000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an olivine-type lithium phosphate-based positive electrode active material. [Background technology]
[0002] Lithium ion secondary batteries have established their position as high-capacity, lightweight power sources essential for portable electronic devices, electric vehicles, and the like. In recent years, with the increase in power consumption due to the high performance of electronic devices, there is a demand for lithium ion secondary batteries with even higher capacities. As one of the positive electrode materials constituting such batteries, so-called olivine-type lithium phosphate-based positive electrode active materials, such as lithium manganese phosphate and lithium iron phosphate, which have an olivine structure, are known, and many of them are produced by hydrothermal synthesis reactions that require the use of pressure-resistant containers as well as the injection of steam and heating.
[0003] In this context, in order to improve the efficiency of the manufacturing process of olivine-type lithium phosphate-based positive electrode active material, a manufacturing method using a synthesis reaction by microwave irradiation instead of a hydrothermal synthesis reaction has been developed. For example, Patent Document 1 discloses a method for producing lithium transition metal phosphate by irradiating a solid mixture of a transition metal-containing compound, a phosphoric acid-containing compound, and a lithium-containing compound in a molar ratio of Li:Fe:P of approximately 1:1:1 with microwaves. Patent Document 2 discloses a liquid-phase high-speed synthesis method for an olivine-type compound in which a liquid raw material consisting of a Li source raw material, a P source raw material, a metal source raw material, and a solvent is reacted at a low temperature for a short time in a reaction zone irradiated with microwaves. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-52996 A [Patent Document 2] JP 2013-163618 A Summary of the Invention
Problems to be Solved by the Invention
[0005] However, even in the technology described in the above patent document, when irradiating with microwaves, the temperature cannot be sufficiently lowered, and nucleation and grain growth proceed simultaneously, making it difficult to control the particle size of the positive electrode active material. Therefore, there is still room for improvement in manufacturing a positive electrode active material that can sufficiently enhance battery characteristics while improving the efficiency of the manufacturing process.
[0006] Therefore, an object of the present invention is to provide a method for manufacturing an olivine-type lithium phosphate-based positive electrode active material that can sufficiently improve the efficiency of the manufacturing process while exhibiting excellent battery characteristics by using a synthesis reaction at a low temperature by microwave irradiation.
Means for Solving the Problems
[0007] Therefore, as a result of intensive studies to solve the above problems, the present inventor has found that by irradiating with microwaves using lithium triphosphate (Li3PO4) particles, it is possible to perform treatment at a low temperature compared to a general hydrothermal synthesis reaction, and to stably manufacture an olivine-type lithium phosphate-based positive electrode active material that can sufficiently enhance battery characteristics.
[0008] That is, the present invention provides the following formula (X): Li a Mn b Fe c M x PO4···(X) (In formula (X), M represents Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, or Gd. a, b, c, and x satisfy 0 < a ≤ 1.2, 0 ≤ b ≤ 1.2, 0 ≤ c ≤ 1.2, 0 ≤ x ≤ 0.3, and b + c ≠ 0, and a + (valence of Mn) × b + (valence of Fe) × c + (valence of M) × x = 3.) A method for manufacturing an olivine-type lithium phosphate-based positive electrode active material represented by the following steps (I) to (II): (I) A phosphoric acid compound (a), one or more acid compounds (b) selected from sulfuric acid, hydrochloric acid, and nitric acid, a lithium compound (c), and water (d1) are mixed together to obtain a mixed liquid i, to which an alkali compound solution is added to obtain a slurry I, which is then subjected to solid-liquid separation to obtain a slurry having a BET specific surface area of 10 m 2 / g~200m 2 / g of lithium phosphate particles A (II) The obtained trilithium phosphate particles A and water (d2) are mixed to form slurry II. 1 Then, slurry II was prepared. 1 A metal compound (e) containing a manganese compound and / or an iron compound is added to slurry II. 2 After obtaining the above, a process of irradiating the mixture with microwaves at a temperature of 80°C to 120°C to obtain a positive electrode active material precursor. The present invention provides a method for producing an olivine-type lithium phosphate-based positive electrode active material, comprising the steps of: Effect of the Invention
[0009] The production method of the present invention makes it possible to obtain a positive electrode active material precursor that can improve the efficiency of the production process by irradiating microwaves at a sufficiently low temperature range while controlling the physical properties of the trilithium phosphate particles used, and also makes it possible to easily control the particle size of the olivine-type lithium phosphate-based positive electrode active material obtained from the positive electrode active material, thereby enabling the stable production of an olivine-type lithium phosphate-based positive electrode active material that can effectively improve battery characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below. The method for producing an olivine-type lithium phosphate-based positive electrode active material of the present invention comprises reacting a compound represented by the following formula (X): Li a Mn b Fe c M x PO4···(X) (In formula (X), M represents Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd or Gd. a, b, c, and x satisfy 0 < a ≤ 1.2, 0 ≤ b ≤ 1.2, 0 ≤ c ≤ 1.2, 0 ≤ x ≤ 0.3, and b + c ≠ 0, and represent numbers that satisfy a + (valence of Mn) × b + (valence of Fe) × c + (valence of M) × x = 3.) A method for producing an olivine-type lithium phosphate-based cathode active material represented by the following, comprising the following steps (I) to (II): (I) An alkali compound solution is added to a mixed solution i obtained by mixing a phosphate compound (a), one or more acid compounds (b) selected from sulfuric acid, hydrochloric acid, and nitric acid, a lithium compound (c), and water (d1) to obtain a slurry I, and then the obtained slurry I is subjected to solid-liquid separation to obtain lithium tripolyphosphate particles A having a BET specific surface area of 10 m 2 / g to 200 m 2 / g (II) The obtained lithium tripolyphosphate particles A and water (d2) are mixed to prepare a slurry II 1 , and then a metal compound (e) containing a manganese compound and / or an iron compound is added to the slurry II 1 to obtain a slurry II 2 , and then the slurry II is irradiated with microwaves at a temperature of 80°C to 120°C to obtain a cathode active material precursor.
[0011] The olivine-type lithium phosphate-based cathode active material obtained by the production method of the present invention has the following formula (X): Li a Mn b Fe c M x PO4···(X) (In formula (X), M represents Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd or Gd. a, b, c, and x satisfy 0 < a ≤ 1.2, 0 ≤ b ≤ 1.2, 0 ≤ c ≤ 1.2, 0 ≤ x ≤ 0.3, and b + c ≠ 0, and represent numbers that satisfy a + (valence of Mn) × b + (valence of Fe) × c + (valence of M) × x = 3.) is represented by. That is, in the present invention, by using lithium tripolyphosphate (Li3PO4) particles A having a limited range of BET specific surface area obtained in step (I), the reaction can proceed with such particles A as nuclei, so that grain growth can be moderately slowed down. Then, in the subsequent step (II), if a cathode active material precursor obtained by irradiating microwaves in a sufficiently low temperature range is used, excessive grain growth can be suppressed, and thus an olivine-type lithium phosphate-based cathode active material exhibiting excellent battery characteristics can be obtained. In this way, while enabling the efficiency of the manufacturing process to be improved, a highly useful olivine-type lithium phosphate-based cathode active material can be stably manufactured.
[0012] The olivine-type lithium phosphate-based cathode active material represented by the above formula (X) is an olivine-type lithium phosphate-based cathode active material containing at least manganese (Mn) or iron (Fe) (hereinafter, also referred to as "particle (X)"), and is a secondary particle formed by aggregation of primary particles. In formula (X), M represents Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd or Gd, preferably Mg or Zr. a satisfies 0 < a ≦ 1.2, preferably 0.6 ≦ a ≦ 1.2, more preferably 0.65 ≦ a ≦ 1.15, and still more preferably 0.7 ≦ a ≦ 1.1. b satisfies 0 ≦ b ≦ 1.2, preferably 0.25 ≦ b ≦ 0.8, more preferably 0.35 ≦ b ≦ 0.8. c satisfies 0 ≦ c ≦ 1.2, preferably 0.2 ≦ c ≦ 0.75, more preferably 0.2 ≦ c ≦ 0.65. And b and c satisfy b + c ≠ 0. x satisfies 0 ≦ x ≦ 0.3, preferably 0 ≦ x ≦ 0.15, more preferably 0 ≦ x ≦ 0.1. And a, b, c, and x are numbers that satisfy a + (valence of Mn) × b + (valence of Fe) × c + (valence of M) × x = 3. More specifically, examples of the olivine-type lithium phosphate-based cathode active material represented by the above formula (X) include, for example, LiMnPO4, LiFePO4, LiMn 0.8 Fe 0.2 PO4, LiMn0.1 Fe 0.9 PO4, LiMn 0.8 Fe 0.1 Mg 0.1 PO4, LiMn 0.8 Fe 0.1 Zr 0.05 PO4, etc.
[0013] The step (I) of the production method of the present invention comprises: adding an alkali compound solution to a mixed liquid i obtained by mixing a phosphoric acid compound (a), one or more acid compounds (b) selected from sulfuric acid, hydrochloric acid, and nitric acid (hereinafter also abbreviated as "acid compound (b)"), a lithium compound (c), and water (d1) to obtain a slurry I, and then subjecting the obtained slurry I to solid-liquid separation to obtain a slurry having a BET specific surface area of 10 m 2 / g~200m 2 This is a process for obtaining trilithium phosphate particles A having a molecular weight of 1 / g.
[0014] Examples of the phosphoric acid compound (a) that can be used include orthophosphoric acid (H3PO4, phosphoric acid), metaphosphoric acid, pyrophosphoric acid, triphosphoric acid, tetraphosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, etc. Among these, it is preferable to use phosphoric acid, and it is more preferable to use it as an aqueous solution with a concentration of 70 to 90% by mass.
[0015] The acid compound (b) that can be used is one or more selected from sulfuric acid, hydrochloric acid, and nitric acid, and has the effect of increasing the solubility of the lithium compound (c) while adjusting the pH environment of the mixed liquid I. Among them, from the viewpoint of increasing the solubility of the lithium compound (c), it is preferable to use sulfuric acid, and it is more preferable to use concentrated sulfuric acid having a concentration of 95% by mass or more.
[0016] Examples of the lithium compound (c) that can be used include lithium hydroxide (e.g., LiOH·H2O), lithium carbonate (e.g., Li2CO3), lithium sulfate, lithium acetate, and hydrates thereof. Among these, lithium carbonate is preferred from the viewpoint of controlling the BET specific surface area of the trilithium phosphate particles A within a desired range, and from the viewpoints of improving the efficiency of the production process and reducing the production cost.
[0017] The amount of water (d1) to be mixed is preferably 6 to 25 moles, and more preferably 8 to 18 moles, per mole of phosphorus contained in the phosphate compound (a), from the viewpoints of ensuring the solubility or dispersibility of each component and increasing the production efficiency of the trilithium phosphate particles A.
[0018] The phosphoric acid compound (a), the acid compound (b), the lithium compound (c), and the water (d1) are mixed in advance to obtain a mixed liquid i, and then an alkaline compound solution is added to the mixed liquid i as described below to obtain a slurry I. In the resulting mixed liquid i, the ratio of the molar amount of lithium contained in the lithium compound (c) to the molar amount of phosphorus contained in the phosphate compound (a) (lithium:phosphorus) is preferably 2.5:1 to 3.2:1, more preferably 2.6:1 to 3.1:1, and even more preferably 2.8:1 to 3.05:1. The phosphoric acid compound (a), the acid compound (b), the lithium compound (c), and the water (d1) may be mixed in amounts that satisfy the above quantitative relationship to prepare a mixed solution i, and then, as described below, an alkaline compound solution may be added to the obtained mixed solution i to obtain a slurry I.
[0019] The order in which the phosphoric acid compound (a), the acid compound (b), the lithium compound (c), and the water (d1) are mixed is not particularly limited. From the viewpoint of ensuring the solubility or dispersibility of each component, however, it is preferable to mix the phosphoric acid compound (a), the acid compound (b), and the water (d1) and then add the lithium compound (c) to the resulting mixed solution and mix them.
[0020] Next, an alkaline compound solution is added to the obtained mixed solution i. This makes it possible to control the BET specific surface area of the trilithium phosphate particles A. Examples of the alkaline compound solution that can be used include an aqueous solution containing sodium hydroxide or an aqueous solution containing potassium hydroxide.
[0021] When adding the alkali compound solution, it is preferable to drop the alkali compound solution into the mixed solution I. The dropping speed of the alkali compound solution is preferably 0.03 mol / min to 4 mol / min, more preferably 0.04 mol / min to 3 mol / min, based on the molar amount of the alkali compound contained in the alkali compound solution dropped into the mixed solution I.
[0022] The pH of the resulting slurry I at 25°C is preferably -1 to 3, more preferably -1 to 2.5, and even more preferably -1 to 2.0, from the viewpoint of increasing the production efficiency of the trilithium phosphate particles A and controlling the BET specific surface area of the trilithium phosphate particles A within a desired range.
[0023] Next, the obtained slurry I is subjected to solid-liquid separation and precipitate recovery to obtain trilithium phosphate particles A in high yield. Examples of devices used for solid-liquid separation include a Buchner funnel, a filter press, a centrifugal filter, a vacuum filter, etc. Among them, it is preferable to use a Buchner funnel or a filter press from the viewpoint of efficiently obtaining Li3PO4 particles.
[0024] The obtained precipitate is preferably further washed with water to obtain a cake, which is then filtered to isolate trilithium phosphate particles A. The amount of water used in washing is preferably 50 to 2000 parts by mass, more preferably 100 to 1500 parts by mass, per part by mass of trilithium phosphate particles A. The particles may be dried after washing. Examples of such drying methods include vacuum drying, spray drying, box drying, fluidized bed drying, external heat drying, and freeze drying. Among these, box drying is preferred.
[0025] The BET specific surface area of the resulting lithium triphosphate particles A is 10 m from the viewpoint of achieving efficient manufacturing process while also achieving excellent battery characteristics. 2 / g~200m 2 / g, preferably 13m 2 / g~180m 2 / g, more preferably 15m 2 / g~150m2 The BET specific surface area of the trilithium phosphate particles A means a value determined from an adsorption isotherm by a nitrogen adsorption method.
[0026] In addition, the average particle size of lithium triphosphate particles A (D 50 ) is preferably 1.0 μm to 12 μm, more preferably 1.5 μm to 12.0 μm, and further preferably 2.0 μm to 12.0 μm. The "average particle size" of the trilithium phosphate particles A is the D 50 The values shown are the particle diameters (median diameters) at 50% of the cumulative particle size.
[0027] The manufacturing method of the present invention includes (II) mixing the lithium triphosphate particles A obtained in step (I) and water (d2) to obtain a slurry II. 1 Then, slurry II was prepared. 1 A metal compound (e) containing a manganese compound and / or an iron compound is added to slurry II. 2 After obtaining the above, the mixture is irradiated with microwaves at a temperature of 80° C. to 120° C. to obtain a positive electrode active material precursor.
[0028] Slurry II 1 In preparing the above, the amount of water (d2) to be mixed is preferably 1.5 to 8 parts by mass, and more preferably 2 to 5 parts by mass, per part by mass of the trilithium phosphate particles A, from the viewpoint of ensuring the solubility or dispersibility of each component and from the viewpoint of increasing the production efficiency of the olivine-type lithium phosphate-based positive electrode active material.
[0029] In addition, Slurry II 1 Before adding the metal compound (e) containing a manganese compound and / or an iron compound to the slurry II, 1 The stirring time is preferably 1 minute to 180 minutes, and more preferably 5 minutes to 120 minutes.
[0030] Next, Slurry II 1A metal compound (e) containing a manganese compound and / or an iron compound is added to the slurry to obtain slurry II. 2 get.
[0031] As the metal compound (e), a manganese compound, an iron compound, or a compound of a metal other than a manganese compound and an iron compound (M: M has the same meaning as M in formula (X)) may be used according to the olivine-type lithium phosphate-based positive electrode active material represented by formula (X). These metal compounds (e) may contain at least a manganese compound or an iron compound, and may further contain one or more metal (M) compounds other than a manganese compound and an iron compound.
[0032] Examples of such metal compounds (e) include metal halide salts such as fluorides, chlorides, and iodides, metal sulfates, as well as organic acid metal salts and hydrates thereof. Of these, the organic acid constituting the organic acid metal salt is preferably an organic acid having 1 to 20 carbon atoms, more preferably an organic acid having 2 to 12 carbon atoms. More preferably, dicarboxylic acids such as oxalic acid and fumaric acid, hydroxycarboxylic acids such as lactic acid, and fatty acids such as acetic acid are included.
[0033] Slurry II 1 From the viewpoint of increasing the production efficiency of the olivine-type lithium phosphate-based positive electrode active material, the ratio of the molar amount of the trilithium phosphate particles A in the lithium phosphate-based positive electrode active material (Li3PO4:(Mn+Fe)) to the molar amounts of manganese and iron in the metal compound (e) to be added is preferably 0.95:1 to 1.05:1, more preferably 0.96:1 to 1.04:1, and even more preferably 0.97:1 to 1.03:1.
[0034] In addition, Slurry II 1When adding the metal compound (e), an antioxidant may be added as necessary. As such an antioxidant, sodium sulfite (Na2SO3), sodium hydrosulfite (Na2S2O4), ammonia water, etc. can be used. The amount of the antioxidant added is preferably 0.01 to 1 mol, more preferably 0.03 to 0.5 mol, per mol of the metal compound (e), from the viewpoint of preventing inhibition of production of the olivine-type lithium phosphate-based positive electrode active material due to excessive addition.
[0035] Obtained slurry II 2 From the viewpoint of improving the efficiency of the production process, the solid content concentration is preferably 10% by mass to 80% by mass, more preferably 15% by mass to 75% by mass, and further preferably 20% by mass to 75% by mass. In addition, Slurry II 2 It is preferable to add the metal compound (e) containing a manganese compound and / or an iron compound and then stir the mixture. The stirring time is preferably 1 to 60 minutes, more preferably 3 to 45 minutes.
[0036] Obtained slurry II 2 From the viewpoint of increasing the production efficiency of the olivine-type lithium phosphate-based positive electrode active material, the pH at 25° C. is preferably 4.8 to 7.0, more preferably 5.0 to 6.8, and further preferably 5.5 to 6.5.
[0037] Next, the obtained slurry II 2 The mixture is irradiated with microwaves at a temperature of 80° C. to 120° C. This enables a synthesis reaction to occur at a low temperature, and while the efficiency of the production process is sufficiently improved, it is possible to obtain a positive electrode active material precursor for producing a highly useful olivine-type lithium phosphate positive electrode active material.
[0038] The temperature during microwave irradiation is 80°C to 120°C. In addition, when irradiating with microwaves, Slurry II 2The above temperature means the temperature measured by a radiation thermometer attached to the inside surface of the microwave generator. 2 When the above is stored in a sealed container, there is no need to apply pressure, which enables a simple and efficient synthesis reaction. Slurry stored in a sealed container II 2 It is preferable to stir the mixture in the above-mentioned manner. The stirring is preferably performed by a planetary system with the central part of the microwave generator as the axis.
[0039] The frequency of the irradiated microwaves is preferably 2 GHz to 30 GHz, and more preferably 2.45 GHz to 30 GHz. The microwave irradiation time is preferably 1 to 60 minutes, more preferably 3 to 60 minutes, and even more preferably 5 to 60 minutes, from the viewpoint of producing a highly useful olivine-type lithium phosphate-based positive electrode active material while fully improving the efficiency of the production process.
[0040] The slurry after microwave irradiation is subjected to solid-liquid separation in the same manner as trilithium phosphate particles A, and the resulting precipitate is washed with water to obtain a cake, which is then filtered and dried to obtain a positive electrode active material precursor.
[0041] The positive electrode active material precursor obtained in the step (II) is further subjected to the following step (III): (III) A step of mixing the positive electrode active material precursor obtained in step (II), a carbon source (f) and water, followed by drying and calcining the resulting powder. It is preferable to obtain an olivine-type lithium phosphate-based positive electrode active material through the above-mentioned process, which can be used as a material for the positive electrode of a lithium ion secondary battery that can effectively improve the battery characteristics.
[0042] The fiber diameter of the cellulose nanofiber that can be used is 1 nm to 1000 nm, and the cellulose molecular chains that constitute it form a periodic structure of carbon. Therefore, by carbonizing the cellulose nanofiber and supporting it on the olivine-type lithium phosphate-based positive electrode active material, it is possible to effectively suppress the deterioration of the electronic conductive path and effectively improve the battery characteristics.
[0043] Examples of the water-soluble carbonaceous material that can be used include one or more selected from sugars, polyols, polyethers, and organic acids. More specifically, examples of the water-soluble carbonaceous material include monosaccharides such as glucose, fructose, galactose, and mannose; disaccharides such as maltose, sucrose, and cellobiose; polysaccharides such as starch and dextrin; polyols and polyethers such as ethylene glycol, propylene glycol, diethylene glycol, polyethylene glycol, butanediol, polyvinyl alcohol, and glycerin; and organic acids such as citric acid, tartaric acid, and ascorbic acid. Among these, from the viewpoint of increasing the solubility and dispersibility in a solvent to effectively function as a carbonaceous material, glucose, fructose, sucrose, and dextrin are preferred, and glucose is more preferred. The water-soluble carbon material, like the cellulose nanofibers, is carbonized to form carbon, which is then supported on the olivine-type lithium phosphate-based positive electrode active material.
[0044] Among these carbon sources (f), from the viewpoint of effectively improving battery characteristics while improving the efficiency of the production process, it is preferable to use cellulose nanofibers and / or glucose, and it is more preferable to use cellulose nanofibers.
[0045] The amount of the carbon source (f) mixed in step (III) is preferably 0.8 to 15 parts by mass, more preferably 1 to 10 parts by mass, in terms of the carbon atom amount of the carbon source (f) relative to 100 parts by mass of the olivine-type lithium phosphate-based positive electrode active material. Examples of the device used for solid-liquid separation include a stirrer, an agitation mixer, a rotary powder mixer, an agitation powder mixer, a planetary mill, a ball mill, a bead mill, and an attritor mill. Among them, mixing and grinding using a planetary mill, a ball mill, a bead mill, or an attritor mill is preferred. The calcination in step (III) is preferably carried out under an inert gas atmosphere or reducing conditions at 400° C. or higher, preferably 400° C. to 800° C., for 5 minutes to 3 hours, preferably 0.3 hours to 1.5 hours. The calcination apparatus may be any heating furnace capable of controlling the atmosphere, such as a box furnace or an externally heated rotary kiln.
[0046] The average particle size (D 50 ) is preferably 1 μm to 12 μm, and more preferably 2 μm to 12 μm. Note that, in the olivine-type lithium phosphate-based positive electrode active material, the "average particle size" is the D 50 The values shown are the particle diameters (median diameters) at 50% of the cumulative particle size. In addition, the BET specific surface area of the resulting olivine-type lithium phosphate-based positive electrode active material is preferably 14 m from the viewpoint of exhibiting excellent battery characteristics. 2 / g~50m 2 / g, more preferably 14m 2 / g~30m 2 The BET specific surface area of the olivine-type lithium phosphate-based positive electrode active material means a value determined from an adsorption isotherm by a nitrogen adsorption method, similar to the BET specific surface area of the trilithium phosphate particles A.
[0047] The olivine-type lithium phosphate-based positive electrode active material of the present invention is a material used as a positive electrode active material for lithium ion secondary batteries. Specifically, for example, the olivine-type lithium phosphate-based positive electrode active material of the present invention is kneaded with acetylene black, ketjen black, polyvinylidene fluoride, N-methyl-2-pyrrolidone, etc. to prepare a positive electrode slurry, which is then applied to a current collector and press-molded to produce a positive electrode. The lithium ion secondary battery to which the positive electrode obtained using the olivine-type lithium phosphate-based positive electrode active material of the present invention can be applied is not particularly limited as long as it essentially comprises a positive electrode, a negative electrode, an electrolyte, and a separator, or a positive electrode, a negative electrode, and a solid electrolyte.
[0048] The olivine-type lithium phosphate-based positive electrode active material of the present invention is in the form of highly pure and fine particles, and therefore can provide a highly useful positive electrode.
[0049] Here, the negative electrode is not particularly limited in terms of its material composition, and any known material composition can be used, as long as it can absorb lithium ions during charging and release them during discharging. For example, lithium metal, graphite, silicon-based (Si, SiOx), lithium titanate, or carbon materials such as amorphous carbon can be used. It is preferable to use an electrode formed of an intercalation material capable of electrochemically absorbing and releasing lithium ions, particularly a carbon material. Furthermore, two or more of the above negative electrode materials may be used in combination, and for example, a combination of graphite and silicon-based materials can be used.
[0050] The electrolyte solution is prepared by dissolving a supporting salt in an organic solvent. The organic solvent is not particularly limited as long as it is an organic solvent that is usually used in electrolytes for lithium ion secondary batteries, and examples of the organic solvent that can be used include carbonates, halogenated hydrocarbons, ethers, ketones, nitriles, lactones, and oxolane compounds.
[0051] The supporting salt is not particularly limited in type, but is preferably at least one of inorganic salts selected from LiPF6, LiBF4, LiClO4, and LiAsF6, derivatives of such inorganic salts, organic salts selected from LiSO3CF3, LiC(SO3CF3)2, LiN(SO3CF3)2, LiN(SO2C2F5)2, and LiN(SO2CF3)(SO2C4F9), and derivatives of such organic salts.
[0052] The separator serves to electrically insulate the positive and negative electrodes and to retain the electrolyte, and may be, for example, a porous synthetic resin film, particularly a porous film of a polyolefin polymer (polyethylene, polypropylene).
[0053] The solid electrolyte electrically insulates the positive and negative electrodes and exhibits high lithium ion conductivity. 0.51 Li 0.34 TiO 2.94 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li7La3Zr2O 12 , 50Li4SiO4 50Li3BO3, Li 2.9 PO 3.3 N 0.46 , Li 3.6 S 0.6 P 0.4 O4, Li 1.07 Al 0.69 Ti 1.46 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3, Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, 30Li2S 26B2S3 44LiI, 63Li2S 36SiS2 1Li3PO4, 57Li2S 38SiS2 5Li4SiO4, 70Li2S 30P2S5, 50Li2S 50GeS2, Li7P3S 11 , Li 3.25 P 0.95 Just use S4.
[0054] The shape of the lithium ion secondary battery having the above-mentioned configuration is not particularly limited, and may be various shapes such as a coin type, a cylindrical type, a square type, or an irregular shape enclosed in a laminate exterior body. EXAMPLES
[0055] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples.
[0056] Li3PO4 particles were produced according to each production example. The BET specific surface area and average particle size (D 50 ) are shown in Table 1.
[0057] [Production Example 1: Production of Li3PO4-A particles] 124.6g of phosphoric acid (85% purity, manufactured by Kanto Chemical Co., Ltd.), 73.6g of sulfuric acid (96% purity, manufactured by Kanto Chemical Co., Ltd.), and 270g of water were placed in a 2L plastic container and stirred for 5 minutes using a stirring blade to prepare a mixed solution i-1. Next, 59.9g of lithium carbonate (99.95% purity, manufactured by Kanto Chemical Co., Ltd.) was added to the resulting mixed solution i-1 at a rate of 20g / min, and the mixture was stirred for 15 minutes using a stirring blade to completely dissolve the lithium carbonate. Then, 180.09g of sodium hydroxide aqueous solution (48% purity, manufactured by Kanto Chemical Co., Ltd.) was added at a rate of 30g / min to obtain a slurry I-1. The obtained slurry I-1 was subjected to solid-liquid separation using a Buchner funnel, and the obtained solid was then washed with 1L of water to obtain a Li3PO4 cake, which was then dried in a thermostatic bath at 100°C for 12 hours to obtain Li3PO4-A particles.
[0058] [Production Example 2: Production of Li3PO4-B particles] Li3PO4-B particles were obtained in the same manner as in Production Example 1, except that the rate at which the aqueous sodium hydroxide solution was added was set to 200 g / min.
[0059] [Production Example 3: Production of Li3PO4-C particles] Li3PO4-C particles were obtained in the same manner as in Production Example 1, except that the rate at which the aqueous sodium hydroxide solution was added was 15 g / min.
[0060] [Production Example 4: Production of Li3PO4-D particles] Li3PO4-D particles were obtained in the same manner as in Production Example 1, except that the rate at which the aqueous sodium hydroxide solution was added was set to 5 g / min.
[0061] [Table 1]
[0062] Each of the above Li3PO4 particles was used to produce each of the positive electrode active materials. The average particle size (D 50 ) and the results of the evaluation of the presence or absence of heterogeneous phases by XRD analysis, as well as the results of the evaluation of the discharge capacity of the lithium ion secondary battery, are shown in Table 2. 2 The solid content concentration and the BET specific surface area of each of the obtained positive electrode active materials are shown in Table 3.
[0063] The BET specific surface area of the positive electrode active material was measured using a flow type automatic specific surface area measuring device (FlowSorbIII2305, manufactured by Shimadzu Corporation) with a nitrogen-helium mixed gas containing 30% nitrogen. Average particle size of the positive electrode active material (D 50 ) was measured for particle size distribution using a laser diffraction device (Microtrac MT3000II, MicrotracBEL) under the following measurement conditions: particle transmittance: transmission, particle shape: non-spherical, particle refractive index: 1.52, ethanol was used as the solvent, and the solvent refractive index: 1.36.
[0064] [Example 1] 11.6 g of the Li3PO4-A particles obtained in Production Example 1 and 30 g of water were mixed and stirred for 5 minutes to obtain Slurry II. 1 The obtained slurry II was prepared as follows: 1Add 16.9 g of MnSO4·5H2O and 8.34 g of FeSO4·7H2O to x1 and stir for 5 minutes to obtain Slurry II. 2 x1 (pH = 6.1 at 25°C) was obtained. Obtained slurry II 2 The mixture x1 was placed in a fluororesin container and irradiated with microwaves at a temperature of 90° C. for 10 minutes using a microwave heating device (MWS-2, manufactured by Berghof, frequency 2450 MHz) to obtain Slurry II. 3 x1 was obtained. The obtained slurry II 3 x1 was subjected to solid-liquid separation using a Buchner funnel, and the obtained solid was then washed with 500 mL of water to obtain a cake, which was then dried in a thermostatic bath at 100° C. to obtain a positive electrode active material precursor (e1′). 3 g of the obtained positive electrode active material precursor (e1'), 0.85 g of cellulose nanofiber (water content 80%, carbon atom equivalent weight 2.5% by mass), 5 g of water, and 80 g of zirconia balls (φ1 mm) were placed in a planetary ball mill container and mixed at a speed of 400 rpm for 10 minutes using a planetary ball mill (P-5, Fritsch GmbH & Co. KG), and then dried in a thermostatic chamber at 80° C. to obtain a powder. The powder thus obtained was then heated at 700° C. for 1 hour under nitrogen flow (300 mL / min) using a tubular electric furnace (TMF-500N, AS ONE Corporation) to obtain a carbon-supported positive electrode active material (e1) (formula: LiMn 0.7 Fe 0.3 PO4) was obtained.
[0065] [Example 2] A positive electrode active material (e2) supported on carbon was obtained in the same manner as in Example 1, except that microwaves were irradiated at a temperature of 90° C. for 30 minutes using a microwave heating device.
[0066] [Example 3] A positive electrode active material (e3) supported on carbon was obtained in the same manner as in Example 1, except that microwaves were irradiated at a temperature of 80° C. for 10 minutes using a microwave heating device.
[0067] [Example 4] A positive electrode active material (e4) supported on carbon was obtained in the same manner as in Example 1, except that microwaves were irradiated at a temperature of 80° C. for 30 minutes using a microwave heating device.
[0068] [Example 5] A positive electrode active material (e5) supported on carbon was obtained in the same manner as in Example 1, except that microwaves were irradiated at a temperature of 100° C. for 30 minutes using a microwave heating device.
[0069] [Example 6] A positive electrode active material (e6) supported on carbon was obtained in the same manner as in Example 1, except that microwaves were irradiated at a temperature of 110° C. for 30 minutes using a microwave heating device.
[0070] [Example 7] A positive electrode active material (e7) supported on carbon was obtained in the same manner as in Example 1, except that microwaves were irradiated at a temperature of 120° C. for 30 minutes using a microwave heating device.
[0071] [Example 8] Slurry II 1 A positive electrode active material (e8) (formula: LiMnPO4) supported on carbon was obtained in the same manner as in Example 1, except that only 24.14 g of MnSO4·5H2O was added to x1 and no FeSO4·7H2O was added.
[0072] [Example 9] Slurry II 1 A positive electrode active material (e9) (formula: LiFePO4) supported on carbon was obtained in the same manner as in Example 1, except that only 27.80 g of FeSO4·7H2O was added to x1 and no MnSO4·5H2O was added.
[0073] [Example 10] A carbon-supported positive electrode active material (e10) was obtained in the same manner as in Example 1, except that the Li3PO4-B particles obtained in Production Example 2 were used instead of the Li3PO4-A particles.
[0074] [Example 11] A positive electrode active material (e11) carrying carbon was obtained in the same manner as in Example 1, except that the Li3PO4-C particles obtained in Production Example 3 were used instead of the Li3PO4-A particles.
[0075] [Example 12] A positive electrode active material (e12) supported on carbon was obtained in the same manner as in Example 1, except that the Li3PO4-D particles obtained in Production Example 4 were used instead of the Li3PO4-A particles.
[0076] [Example 13] 11.6 g of the Li3PO4-A particles obtained in Production Example 1 and 30 g of water were mixed and stirred for 5 minutes to obtain Slurry II. 1 x 13 The obtained slurry II was 1 x 13 0.25 g of sodium hydroxide solution (Slurry II 1 x 13 Add 16.9 g of MnSO4·5H2O and 8.34 g of FeSO4·7H2O and stir for 5 minutes to obtain Slurry II. 2 x 13 (pH=6.7 at 25° C.) was obtained. Slurry II 2 Instead of x1, the resulting slurry II 2 x 13 A positive electrode active material (e13) supported on carbon was obtained in the same manner as in Example 1, except that the above was used.
[0077] [Example 14] 11.6 g of the Li3PO4-A particles obtained in Production Example 1 and 30 g of water were mixed and stirred for 5 minutes to obtain Slurry II. 1 x 14 The obtained slurry II was 1 x 14 0.35 g of phosphoric acid, 16.9 g of MnSO4·5H2O, and 8.34 g of FeSO4·7H2O were added and stirred for 5 minutes to obtain Slurry II. 2 x 14 (pH=5.0 at 25° C.). Slurry II 2Instead of x1, the resulting slurry II 2 x 14 A positive electrode active material (e14) supported on carbon was obtained in the same manner as in Example 1, except that the above was used.
[0078] [Example 15] Slurry II 1 A positive electrode active material (e15) supported on carbon was obtained in the same manner as in Example 1, except that the amount of water used in preparing x1 was 20 g and microwaves were irradiated at a temperature of 90° C. for 30 minutes using a microwave heating device.
[0079] [Comparative Example 1] Instead of irradiating microwaves with a microwave heating device, Slurry II 2 A positive electrode active material (c1) supported on carbon was obtained in the same manner as in Example 1, except that x1 was placed in an autoclave and held at 160° C. for 60 minutes.
[0080] [Comparative Example 2] A positive electrode active material (c2) supported on carbon was obtained in the same manner as in Example 1, except that microwaves were irradiated at a temperature of 70° C. for 30 minutes using a microwave heating device.
[0081] [Comparative Example 3] Slurry II 2 A positive electrode active material (c3) supported on carbon was obtained in the same manner as in Comparative Example 1, except that x1 was placed in an autoclave and held at 100° C. for 60 minutes.
[0082] [Comparative Example 4] A positive electrode active material was produced without using the Li3PO4 particles obtained in the production example. Specifically, 2.569g (60mmol) of LiOH·H2O, 4.4g (110mmol) of NaOH, and 30mL of water were mixed to obtain a slurry. Next, while the obtained slurry was kept at a temperature of 25°C and stirred for 10 minutes, 6.918g of an 85% aqueous phosphoric acid solution was added dropwise at a rate of 35mL / min, and then stirred for 12 hours to obtain a mixed solution e1 (the ratio of the molar amount of lithium to the molar amount of phosphorus (lithium:phosphorus) = 1:1). To the total amount of the obtained mixed solution e1, 10.1g of MnSO4·5H2O and 5.00g of FeSO4·7H2O were added to obtain mixed solution e2 (pH 4.3). At this time, the molar ratio of added MnSO4 to FeSO4 was 7:3. The obtained mixed solution e2 was stirred at 90°C under atmospheric pressure for 12 hours to proceed the reaction and obtain the positive electrode active material precursor (c4'). A carbon-supported positive electrode active material (c4) was obtained in the same manner as in Example 1, except that the positive electrode active material precursor (c4') was used instead of the positive electrode active material precursor (e1').
[0083] [Comparative Example 5] A positive electrode active material was produced without using the Li3PO4 particles obtained in the production example. Specifically, 10 mmol of each of CH3COOLi·2H2O (Wako Pure Chemical special grade), Mn(CH3COO)2·4H2O (Wako Pure Chemical special grade), and NH4H2PO4 (Wako Pure Chemical special grade) were weighed and added to 40 mL of distilled water to obtain mixed solution e5. Slurry II 2 A carbon-supported positive electrode active material (c5) was obtained in the same manner as in Example 1, except that the obtained mixed liquid e5 was used instead of x1.
[0084] Observation of the formation phase (presence or absence of heterogeneous phases) The resulting positive electrode active material was analyzed by XRD (X-ray diffraction measurement device (D8-Advance, manufactured by BRUKER)) to observe the produced phase and evaluate the presence or absence of a different phase. Specifically, the measurement conditions were as follows: target CuKα, tube voltage 35 kV, tube current 350 mA, scanning range 10° to 80° (2θ), step width 0.02°, and scan speed 0.13 seconds / step. Based on the obtained chart, the crystal phases were identified by matching each peak (2θ) with the crystal phase having the corresponding interplanar spacing, and the presence or absence of heterogeneous phases was confirmed.
[0085] <Evaluation of discharge capacity> Using the obtained positive electrode active material, a positive electrode of a lithium ion secondary battery was first produced. Specifically, the obtained positive electrode active material, acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 90:5:5, and N-methyl-2-pyrrolidone was added to this and thoroughly kneaded to prepare a positive electrode slurry. The positive electrode slurry was applied to a current collector made of aluminum foil with a thickness of 20 μm using a coater, and vacuum dried at 80 ° C for 12 hours. Thereafter, it was punched into a disk shape of φ14 mm and pressed for 2 minutes at 16 MPa using a hand press to produce a positive electrode. Next, a coin-type lithium ion secondary battery was constructed using the above positive electrode. A lithium foil punched to φ15 mm was used as the negative electrode. The electrolyte was a mixture of ethylene carbonate and ethyl methyl carbonate mixed at a volume ratio of 1:1, in which LiPF6 was dissolved at a concentration of 1 mol / L. The separator was a known one made of a polymer porous film such as polypropylene. These battery components were assembled and housed in an atmosphere with a dew point of -50°C or less by a conventional method, to produce a coin-type lithium ion secondary battery (CR-2032).
[0086] The obtained lithium-ion secondary battery was used to carry out charge-discharge tests at a constant current density. Specifically, after constant current charging at a current of 0.2 CA (34 mAh / g) and a voltage of 4.5 V, it was discharged at a constant current of 3 CA and a cut-off voltage of 2.0 V. All charge-discharge tests were carried out at 30°C.
[0087] [Table 2]
[0088] [Table 3]
Claims
1. The following formula (X): Li a Mn b Fe c M x 2O 4 ・・・(X) (In formula (X), M represents Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, or Gd. a, b, c, and x represent numbers that satisfy 0<a≦1.2, 0≦b≦1.2, 0≦c≦1.2, 0≦x≦0.3, and b+c≠0, and that satisfy a+(valence of Mn)×b+(valence of Fe)×c+(valence of M)×x=3.) A method for producing an olivine-type lithium phosphate-based positive electrode active material represented by the following steps (I) to (II): (I) A phosphoric acid compound (a), one or more acid compounds selected from sulfuric acid, hydrochloric acid, and nitric acid (b), a lithium compound (c), and water (d1) are mixed to obtain a mixed liquid i, to which an alkali compound solution is added to obtain a slurry I, which is then subjected to solid-liquid separation to obtain a slurry having a BET specific surface area of 10 m 2 / g to 200m 2 / g of trilithium phosphate particles A (II) The obtained trilithium phosphate particles A and water (d2) are mixed to obtain slurry II. 1 Then, slurry II was prepared. 1 A metal compound (e) containing a manganese compound and / or an iron compound was added to the slurry to obtain slurry II. 2 After obtaining the above, a step of irradiating the mixture with microwaves at a temperature of 80° C. to 120° C. to obtain a positive electrode active material precursor. The method for producing an olivine-type lithium phosphate-based positive electrode active material comprises the steps of:
2. Further, the next step (III): (III) A step of mixing the positive electrode active material precursor obtained in step (II), a carbon source (f) and water, followed by drying and calcining the resulting powder. The method for producing an olivine-type lithium phosphate-based positive electrode active material according to claim 1 , comprising:
3. In step (II), slurry II 1 The molar amount of lithium phosphate particles A in slurry II 1 The molar ratio of manganese and iron in the metal compound (e) added to the 3 P.O. 4 3. The method for producing an olivine-type lithium phosphate-based positive electrode active material according to claim 1, wherein the ratio of Mn to Fe is 0.95:1 to 1.05:
1.
4. Slurry II in step (II) 2 The method for producing an olivine-type lithium phosphate-based positive electrode active material according to any one of claims 1 to 3, wherein the solid content concentration is 10% by mass to 80% by mass.
5. The method for producing an olivine-type lithium phosphate-based positive electrode active material according to any one of claims 1 to 4, wherein in the slurry I obtained in step (I), the ratio of the molar amount of lithium contained in the lithium compound (c) to the molar amount of phosphorus contained in the phosphate compound (a) (lithium:phosphorus) is 2.5:1 to 3.2:
1.
6. In step (II), slurry II 2 The method for producing an olivine-type lithium phosphate-based positive electrode active material according to any one of claims 1 to 5, wherein the pH at 25°C is 4.8 to 7.0.
Citation Information
Patent Citations
Method for preparing columnar LiFePO4 crystals through ultrasonic solvent thermal and microwave hydrothermal method
CN102502564A
Active material, method of manufacturing active material, and lithium ion secondary battery
JP2011009190A
POSITIVE ELECTRODE ACTIVE MATERIAL FOR Li-ION CELL AND METHOD OF MANUFACTURING THE SAME
JP2011204638A
Liquid phase high speed synthesis method for olivine type compound or carbon composite thereof
JP2013163618A
Method for preparing transition metal lithium phosphate
JP2016052996A